Molecular mechanisms and comparative transcriptomics of diapause in two corn rootworm species (Diabrotica spp.) - Melise C. Lecheta; Chad Nielson; B. Wade French; Emily A.W. Nadeau; Nicholas M. Teets (Current Research in Insect Science)
Diapause is a programmed developmental arrest that can occur at any developmental stage depending on species, but the mechanisms that underscore embryonic diapause are poorly understood. Here, we identified molecular mechanisms underscoring distinct phases of diapause in the Diabrotica spp. complex. This species complex includes economically significant agricultural pests, notably the western corn rootworm (WCR) and northern corn rootworm (NCR), which cause major losses in maize production. Rootworms undergo an obligate embryonic diapause to synchronize their life cycles with host plants, and we sequenced transcriptomes from both species at five time points (pre-diapause, diapause initiation, diapause maintenance, diapause termination, and post-diapause). Our results indicate that transcriptional regulation is dynamic during diapause. Diapause initiation involves shutdown of the cell cycle by downregulating cyclin-related genes, downregulation of aerobic metabolism, with concurrent upregulation of stress-related genes, especially heat shock proteins, the proteasome, and immune-related genes. During post-diapause development, there is a dramatic activation cellular respiration, which may be controlled by insulin signaling. Comparative transcriptomic analyses between WCR and NCR indicated that while many gene expression changes were conserved across species, overall gene expression profiles were distinct, indicating that many transcriptional changes are species-specific, despite the close phylogenetic relationship and phenotypic similarity between these species. This study sheds light on the suite of mechanisms that allow some organisms to pause the symphony of cellular events that occur during embryonic development and persist for several months as a tiny egg. Further, the mechanisms identified here may contribute to further research and pest management efforts in this economically important pest group.